Уровень жизни населения северного региона и пути его повышения (на примере Республики Саха (Якутия)) : The Standards of Living of a Northern Region and Ways of Their Improvement (by the Example of the Republic of Sakha (Yakutiya)) - Толстых Геннадий Владимирович (Уровень жизни населения регионов России, 2019)
Объект – северный регион (Республика Саха (Якутия)) Предмет – уровень жизни населения Республики Саха (Якутия) Цель данной статьи – выявление наиболее важных проблем уровня жизни населения северного региона (на примере Республики Саха (Якутия)) и определение путей его повышения Методы исследования: анализ государственной статистики и данных органов государственного управления по вопросам демографического развития, изменения динамики доходов населения, прожиточного минимума, ожидаемой продолжительности жизни и т.д. Установлено, что устойчивое развитие северных регионов может осуществляться за счёт повышения уровня жизни населения и это является одним из условий обеспечения национальной безопасности России. Больше половины общей площади страны относится к северным территориям. Регионы Севера дают 60% всех валютных поступлений РФ. Переход к рыночным отношениям ощутимо повлиял на ухудшения качества социальной инфраструктуры Севера. За последние 15 лет все субъекты ДВФО , кроме Республики Саха (Якутия) потеряли численность своего населения. Причины миграционного оттока – снижение материальных стимулов работы на Крайнем Севере. Наблюдается ограниченный доступ к качественным медицинским, образовательным и культурным услугам. Благодаря принимаемым мерам, в период с 2002-2016 гг. удалось увеличить ожидаемую продолжительность жизни (ОПЖ) на 7 лет в Республике Саха (Якутия), Хабаровском крае, Амурской и Магаданской областях. У Республики Саха (Якутия) имеется целый ряд нерешённых проблем, которые являются сдерживающими факторами повышения уровня жизни населения северного региона – высокая стоимость проезда в отпуск в летний сезон, значительная доля ветхого и аварийного жилья в общем жилищном фонде, низкое качество питьевой воды и др. Для их решения необходима поддержка федеральных органов государственной власти. : The Object of the Study is a northern territory (the Republic of Sakha (Yakutiya). The Subject of the Study the living standards of the population of the Republic of Sakha (Yakutiya). The Purpose of the Study is to identify the most important problems of the standards of living of a northern region (by the example of the Republic in Sakha (Yakutiya)) and finding ways of their improvement. Methods of Investigation: analysis of the statistics and the data of the public bodies of the State administration on the issues of demographic development, changes in the dynamics of incomes of the population, subsistence minimum, life expectancy, etc. It is found that sustainable development of northern regions can be achieved by raising the standards of living of the population and this is one of the conditions for ensuring national security of Russia. More than half of the total area of the country belongs to the northern territories. The regions of the North give 60% of all foreign exchange earnings of the Russian Federation. The transition to market relations significantly affected the deterioration of the quality of the social infrastructure of the North. Over the past 15 years, all subjects of the Far Eastern Federal District, except for the Republic of Sakha (Yakutiya), have lost their population. The reasons for the migration outflow are the reduction of material incentives for work in the Far North. There is a limited access to quality medical, educational and cultural services. Thanks to the measures taken, in the period of 2002-2016 life expectancy increased by 7 years in the Republic of Sakha (Yakutiya), Khabarovskiy Kray, Amur and Magadan Oblast’s. The Republic of Sakha (Yakutiya) has a number of unresolved problems that are deterrent factors in raising the living standards of the population of the northern region which are a high cost of travel on vacation during summer season, a significant proportion of old and dilapidated housing in the general housing stock and poor quality of drinking water. To solve these problems it is necessary a support of the federal bodies of the state power.